Synthesis of 9,9′-Bifluorenylidene-Based Porous Aromatic Frameworks (BF-PAFs) for Photocatalytic Production of Hydrogen Peroxide - Wang, He; Xu, Xinmeng; Cao, Linzhu; Tao, Xin (Synthesis, 2024)
Photocatalytic technology is considered to be a sustainable strategy to convert H2O and O2 into H2O2. However, constructing photocatalytically active and stable organic photocatalyst remain a challenge. In this study, a new class of porous aromatic framework photocatalysts (BF-PAFs) were designed and synthesized, in which 9,9′-bifluorenylidene (99′-BF) and different alkynes are alternately connected. The BF-PAFs were constructed and served as photocatalysts for H2O2 synthesis. Experimental results show that the introduction of different alkynes can effectively regulate the optical band gap and energy band structure, which may further determine their photocatalytic performance. Upon visible light irradiation, PAF-370 exhibits high efficiency for photosynthesis of H2O2 with a production rate of 730 μmol g–1 h–1 in the presence of sacrificial reagent from water and oxygen via oxygen reduction reaction (ORR) pathway. Furthermore, up to 61 μmol H2O2 could be generated from this photocatalytic system after 14 hours.
Keywords: porous aromatic framework; donor-acceptor; hydrogen peroxide; recyclability; heterogeneous